Ephydrolithus Girón & Short, 2019 (Coleoptera: Hydrophilidae): new species and updated distribution records from Northeast region of Brazil - Amorim-Junior, Gilson P.; Nascimento, Jeane M. C.; Hamada, Neusa (Zootaxa, 2024)
The Neotropical genus Ephydrolithus Girón & Short, 2019 was recently established based on five species. In 2022 five additional species were described, all of them from the Espinhaço Mountain Range, in the states of Minas Gerais and Bahia, Brazil. During an aquatic insect survey in three states in the Northeast region of Brazil, we collected two new species of Ephydrolithus in the states of Bahia, Ceará and Pernambuco, one of the new species collected in the two latter states, represent the first record of this genus outside the Espinhaço Mountain Range, expanding its distribution to other Brazilian states. The objective of this study is to describe two new species of Ephydrolithus based on both male and female specimens. We also provide an updated identification key and distributional maps for the genus.